2005
DOI: 10.1515/ijamh.2005.17.3.267
|View full text |Cite
|
Sign up to set email alerts
|

A model program for youth suicide prevention

Abstract: This study examined the positive and negative self-complexity of suicidal adolescents. Methods·. Thirty-two Israeli suicidal inpatients, thirty-two nonsuicidal inpatients and thirty-two control participants completed scales on self-complexity and suicidal tendencies. Self-complexity was based on Linville's measure and revealed four different aspects of self-complexity: number of positive/negative traits, number of positive/negative/neutral self-aspects, amount of redundancy of the positive/negative traits and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Programs for suicide prevention should be implemented for youth who are at risk for suicide, including those who self-injure themselves. 2,3,22,[98][99][100] More research on deliberate selfharm should be carried out with reference to the research gaps identified in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Programs for suicide prevention should be implemented for youth who are at risk for suicide, including those who self-injure themselves. 2,3,22,[98][99][100] More research on deliberate selfharm should be carried out with reference to the research gaps identified in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Such interventions are aimed at educating the public, medical care providers, schoolteachers, school counselors, youth service center personnel, and other entities that deal with children and adolescents [ 29 ]. Early identifi cation of children at risk by such programs may impact rates of suicide in children, as improved detection of childhood depression may be one of the best ways to reduce child suicide [ 30 ].…”
Section: Community-level Treatmentsmentioning
confidence: 99%
“…However, human behaviour such as grieving is a dynamic process, and, often attempts to model human behaviour fails because most models fail to account for temporal changes and dynamics in behaviour [34]. For example, some high school and community based studies suggest that grief due to suicide is too complex to fit the Kubler-Ross model [35,36].…”
Section: Discussionmentioning
confidence: 99%